2019
DOI: 10.1002/ppul.24419
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and exhaled biomarkers of exercise‐induced bronchoconstriction in atopic asthmatic children

Abstract: Background Exercise‐induced bronchoconstriction (EIB) reflects poor asthma control. Assessing noninvasive biomarkers associated with EIB could help to monitor patients in the pediatric age. Aims To test exhaled and urinary biomarkers for assessing EIB in atopic asthmatic children. Methods In 45 atopic patients (11.1 ± 1.8 years, 25 males) we measured the fractional exhaled nitric oxide (FENO), its alveolar (CaNO), and bronchial (J’awNO) components corrected for the trumpet shape of the airways and axial NO dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Similar inflammatory changes in the respiratory passages were revealed when examining long-distance runners [30]. A positive correlation was also detected between the exhaled NO index immediately after doing an exercise and the degree of bronchial inflammatory infiltration [24,33]. An independent pathogenetic factor in bronchial asthma and EIB development in athletes is the atopy and its severity.…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagerssupporting
confidence: 60%
See 1 more Smart Citation
“…Similar inflammatory changes in the respiratory passages were revealed when examining long-distance runners [30]. A positive correlation was also detected between the exhaled NO index immediately after doing an exercise and the degree of bronchial inflammatory infiltration [24,33]. An independent pathogenetic factor in bronchial asthma and EIB development in athletes is the atopy and its severity.…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagerssupporting
confidence: 60%
“…It is now considered proven that bronchial asthma associated with EIB is accompanied by an increase in NO production associated with airway obstruction severity. At the same time, reduced NO production is associated with retrograded EIB clinical signs severity [24]. On the other hand, some literature sources present data showing that there is no identified association between the EIB severity and NO production [25].…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagersmentioning
confidence: 99%
“…In addition to the urinary ranges for healthy adults, the urinary ranges of oxidative stress biomarkers in children have also been reported, although there are fewer of these studies in the literature. The reference urinary ranges are 2.63–4.61 ng/mg creatinine for 8-oxodGuo [ [278] , [279] , [280] ], 5.58–12.5 ng/mg creatinine for 8-oxoGuo [ [280] , [281] , [282] ], and 11.5–17.8 ng/mg creatinine for 8-oxoGua [ 281 , 283 ].…”
Section: Nucleic Acid Oxidation In Human Health and Diseasementioning
confidence: 99%
“…Other biomarkers have also been postulated to identify patients with asthma. One group compared patients with atopic asthma to controls and found that both urinary adenosine and peripheral airway exhaled nitric oxide were significantly higher in the group with asthma 4 . Additionally, within the group of subjects with atopic asthma, those with exercise‐induced bronchoconstriction (EIB) had higher measurements of both noninvasive inflammatory biomarkers.…”
Section: Year In Review: Asthmamentioning
confidence: 99%